The Influence Of Self-Efficacy On Employee Performance With Job Satisfaction As An Intervening Variable At Mawar Bakery & Cake Shop Medan - Sanjaya, Taufan; Syahyunan, Syahyunan; Saskia, Saskia (Cattleya Darmaya Fortuna, 2025)
This study aims to explore the impact of self-efficacy on job satisfaction, as well as the individual effects of self-efficacy and job satisfaction on employee performance. Additionally, it seeks to assess how self-efficacy influences employee performance via job satisfaction at Mawar Bakery & Cake Shop. The research involved a sample of 100 individuals, all of whom were selected through purposive sampling. Path analysis was employed for data analysis. The findings indicate that self-efficacy has a positive and significant impact on employee performance, job satisfaction positively affects employee performance, self-efficacy significantly influences job satisfaction, and self-efficacy positively impacts employee performance through job satisfaction.